THE TRANSLATION ANALYSIS ON ACER ASPIRE 4520/4220 SERIES EMPOWERING TECHNOLOGY USER'S GUIDE - Faizal Lutvi Hidayat, - (2008)
Translation is a demanding job for the translators recently since new terms in various area of translation work were popped out especially in information and technology area. Furthermore, the theories for the translation field were not regenerated continuously. Translation theories are really needed to give some directions in solving the problems. In learning a foreign language, the ability in translation is a plus mark. The research which entitled The Translation Analysis on Acer ASPIRE 4520/4220 Series Empowering Technology User's Guide was aimed to find out the translation procedures and methods mostly engaged by the translator in producing the translated text. The translated version of Acer ASPIRE 4520/4220 User's Guide as an example of vocative text is the object of this research. The aims of this research are (1) to find out about the translation procedures used in translating the Acer ASPIRE 4520/4220 User's Guide, and (2) to find out about translation method used by the translator of Acer ASPIRE 4520/4220 User's Guide. This study used descriptive qualitative method through several techniques. First, reading the original and the translated versions to obtain the data of the translation procedures and translation methods. Second, analyzing and classifying the data into the classification of translation procedures and translation methods according to Newmark. The data were analyzed and interpreted by using descriptive explanation. The result of this study showed that several translation procedures and methods were applied in translating the chosen units of translation of the original version: for the translation procedures out of twenty procedures, the researcher only found ten translation procedures, those are: transference, naturalization, synonymy, through translation, recognized translation, reduction and expansion, paraphrase, equivalence, couplets and notes, additions, glosses; while for translation methods are word-for-word translation, literal translation, faithful translation, semantic translation, adaptation, free translation, idiomatic translation and communicative translation. Furthermore, from the eight translation methods, there were only seven translation methods that were found in the book. The findings of the research were finally concluded that translation procedure mostly adopted in the book of Acer User's Guide is couplets, and the translation method that mostly found in the book is communicative translation method.